SYSTEM FOR DETECTING INCIDENTS IN BUILDINGS OR VESSELS - BENKEMOUN, Yves; CHAUVIN, David (2020)
The subject matter of the invention is a system for detecting incidents in buildings or vessels, as well as a method for detecting incidents, such as break-ins, damage, water leaks and possibly fire. In particular, the field of the invention relates to walls, façades or ceilings made from plasterboard, wood or cement and comprising such a detection system. The subject matter of the invention is also the use of the detection system for constructing buildings or vessels comprising smart walls. The invention is particularly advantageous since the different incidents can be detected using a single, low-cost, low-consumption system. The system is easy to install when laying walls and is invisible. L'objet de l'invention est un système de détection de sinistres dans les bâtiments terrestres ou marins, ainsi qu'une méthode de détection des sinistres tels que l'intrusion, l'endommagement, les fuites d'eau et éventuellement l'incendie. En particulier, le domaine de l'invention concerne les parois, façades ou plafonds réalisés en plaque de plâtre, bois ou ciment et comportant un tel système de détection. L'objet de l'invention est également l'utilisation du système de détection pour la fabrication de bâtiments comportant des parois intelligentes. L'invention est particulièrement avantageuse car les différents sinistres peuvent être détectés avec un système unique, de faible coût et de faible consommation. Le système est facile à placer lors de la pose des parois et est invisible.